Topology optimization of an oil tanker bulkhead subjected to hydrostatic loads (Journal of Naval Architecture and Marine Engineering, 2021)
In the field of Naval Architecture, the conventional approach to design any vessel is to follow the classification societies’ rules to ensure adequate strength and structural integrity. Nowadays, owners’ demands and purposes of vessels are changing dramatically. To mitigate these demands, sometimes it is necessary to design new types of structures, but the classification society’s rules are not sufficient to prepare these advanced designs. Moreover, Naval Architects are always eager to minimize the lightweight of a vessel as this is directly related to cost and carrying capacity. Topology optimization has become a powerful tool for designing structures in an optimized way. The concept of topology optimization has been utilized by the automotive and aerospace industry for almost thirty years where problems associated with solutions meant to satisfy maximum stiffness and structural integrity with minimum weight which are of utmost importance. However, in the field of marine and offshore structures, the use of topology optimization is infrequent. As structural optimization aims to design structures under certain constraints to achieve better strength and lower cost, the introduction of this technique in ship structure can be lucrative. In this paper, a methodology to apply structural topology optimization in the field of ship design is presented. An Oil Tanker Bulkhead has been selected for this study. SIMULIA ABAQUS software is used in this regard. Topology optimization has been performed by minimizing the strain energy of the component as the objective function and a target stiffness and material volume of the structure as design constraints. Finally, the results demonstrate the general applicability of the methodology presented for obtaining the geometrical layout of the structure.